1985
DOI: 10.1111/j.1432-1033.1985.tb08637.x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of polynucleosome relaxation and ADP‐ribosylation

Abstract: Isolated rat pancreatic polynucleosomes were poly(ADP-ribosylated) with purified calf thymus poly(ADPribose) polymerase. A time course study was performed using an NAD concentration of 200 pM and changes in nucleosomal structure were investigated by means of electron microscopy visualization and sedimentation velocity determinations. In parallel, analyses of histone H1 poly(ADP-ribosylation) and determinations of DNA polymerase CI activity on ADP-ribosylated polynucleosomes were done at different time interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Thus if poly(ADPribosylation) were to be of significance in vivo, one would expect these proteins to be major acceptors. Although any proposal for the significance of the inhibition is clearly speculative, inhibition of topoisomerase II at times of chromatin relaxation resultant from histone HI poly(ADP-ribosylation) (Aubin et al, 1983;Niedergang et al, 1985) might be necessary to restrict the introduction of topological changes in the chromatin. wt.…”
Section: Discussionmentioning
confidence: 99%
“…Thus if poly(ADPribosylation) were to be of significance in vivo, one would expect these proteins to be major acceptors. Although any proposal for the significance of the inhibition is clearly speculative, inhibition of topoisomerase II at times of chromatin relaxation resultant from histone HI poly(ADP-ribosylation) (Aubin et al, 1983;Niedergang et al, 1985) might be necessary to restrict the introduction of topological changes in the chromatin. wt.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been accumulated showing the correlation between the change of chromatin structure and poly-(ADP-ribosyl)ation of histone H1. Electron microscopic studies have revealed that the solenoid chromatin structure was relaxed by the poly(ADP-ribosyl)ation of histone H1 protein exposing internucleosomal DNA regions from the interior of the structure (54,55). De Murcia et al (56) further demonstrated that the degradation of ADP-ribose units on poly(ADP-ribosyl)ated histone H1 by poly(ADP-ribose) glycohydrolase restored the solenoid chromatin structure.…”
Section: Figmentioning
confidence: 99%
“…[3]) and the histone adducts thus formed can be further elongated by poly(ADPribose) polymerase [7]. Mechanistic interpretation of the enzymology of poly-ADP-ribosylation and of important supramolecular events in chromatin that appear to coincide with shifts in protein patterns of ADP-ribosylation [8,9] depend on a more detailed understanding of the initial steps of ADPribosylation at the poly(ADP-ribose) polymerase level [lo]. Pursuing this question, the existence of an early product [l l] was indicated.…”
Section: Introductionmentioning
confidence: 99%